Evolution of strategic management research lines in hospitality and tourism. Issue 6 (18th August 2019) - Köseoglu, Mehmet Ali; Law, Rob; Okumus, Fevzi; Barca, Mehmet; Dogan, Ismail Cagri
ABSTRACT: This study explores the evolution of strategic management research lines in the hospitality and tourism field as a scientific field. To this end, co-word analysis is employed for 2577 strategic management articles related to the hospitality and tourism field that were published in leading hospitality and tourism focused journals and business/management journals. The research lines indicate that the strategic management process has the highest usage percentage, followed by firm performance, industrial organization, theory of firms, and organizational behavior. Research lines, such as cooperative strategy, corporate governance, entrepreneurship, corporate strategy, and internationalization, receive minimal interest amongst researchers. The current study is amongst the first in this field that discusses how research lines in the field could be advanced.